The Harpers’ Legacy: Irish National Airs and Pianoforte Composers - Hunt, Una (Journal of the Society for Musicology in Ireland, 2010)
Ireland’s harpers were part of an ancient culture and they left behind an unique and important legacy of indigenous art. The harpers’ airs enjoyed renewed popularity during the nineteenth century when visiting virtuosi to Ireland extemporized on the best-known melodies. Among these musicians were some of the most highly regarded pianist-composers of the era, including Frédéric Kalkbrenner, Ignaz Moscheles and, later still, Henri Herz, Franz Liszt and Sigismund Thalberg. In addition, a substantial number of pieces were published for the drawing-room market. This article charts the rise and fall in popularity of Irish airs in nineteenth-century piano literature and aims to provide reasons for these trends. It shows that Thomas Moore’s almost universally-known drawing-room songs, the Irish Melodies, exerted an influence. But, while these songs may have prompted significant activity among nineteenth-century Irish and Continental musicians, Moore’s role was by no means exclusive. Irish airs were in vogue in the eighteenth century, and even earlier. A catalogue of around 500 works published between c1770 and c1940, included as an appendix to the article, demonstrates the diversity and surprisingly wide-ranging nature of this virtually unknown repertoire.